Beethoven : Légendes et vérités - Buchet, Edmond (Paris Buchet/Chastel, 1995)
Edmond Buchet wipes the slate clean of the legends built up around the life of this magnified, maligned, but in reality unknown Beethoven. The author blends psychological analysis with musical criticism to highlight Beethoven's genius. (Translated with Deepl.com)
Keywords: Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Composer; Biography; Music history